Elevation of Postmortem Cerebrospinal Fluid Sodium and Chloride Levels Is a Potential Adjunct Test in the Diagnosis of Salt Water Drowning. (September 2019) - Garland, Jack; McCarthy, Sinead; Hensby-Bennett, Sarah; Philcox, Winston; O'Regan, Toni; Rousseau, Guillaume; Palmiere, Cristian; Elstub, Hannah; Cala, Allan; Clifton, Leah; Lam, Leo; Barker, Claire; et al.
Abstract : Abstract: Postmortem vitreous humor biochemistry is a useful test in the diagnosis of salt water drowning (SWD). A significant limitation of vitreous humor is the potential effect of prolonged immersion. A recent animal study and case report suggested that cerebrospinal fluid biochemistry may be an alternative to vitreous because it is more resistant to the effects of immersion, given its protected anatomical location. This study compared postmortem cerebrospinal fluid sodium and chloride (PMCSC) levels collected via ventricular aspiration (PMCSC_V) and via lumbar puncture (PMCSC_L) in 13 SWD and 31 nonimmersion deaths. It showed a significant elevation in PMCSC levels in SWD deaths for both PMCSC_V and PMCSC_L ( P < 0.05). The areas under the curve on the receiver operating characteristic curves for PMCSC_V and PMCSC_L were 0.73 and 0.83, respectively. The optimal cutoff for PMCSC_V was 216 mmol/L (sensitivity, 0.60; specificity, 0.72; likelihood ratio, 1.80; positive predictive value, 0.45) and for PMCSC_L was 241 mmol/L (sensitivity, 0.78; specificity, 0.73; likelihood ratio, 2.89; positive predictive value, 0.46). This study supports PMCSC levels as another biochemical test that can potentially aid in the diagnosis of SWD, particularly in cases where vitreous humor samples are unavailable or uninterpretable. Abstract : Supplemental digital content is available in the text.